Analysis Of The Use Of Village Information Systems (Sid) In Supporting The Acceleration Of Village Development In Pegajahan District, Serdang Bedagai Regency - Reksa Wijaya, Cakra; Sirojuzilam, Sirojuzilam; Badaruddin, Badaruddin (International Journal of Science, Technology & Management, 2023)
The aim of this research is to: 1) analyze the implementation of the Village Information System in Pegajahan District, Pegajahan District, Serdang Bedagai Regency, and 2) analyze the influence of the Village Information System in supporting the acceleration of village development in Pegajahan District, Pegajahan District, Serdang Bedagai District. Research was carried out in Pegajahan District, Serdang Bedagai Regency regarding the Effect of Using Village Information Systems (SID) in Supporting the Acceleration of Village Development in Pegajahan District, Serdang Bedagai Regency. The analytical method used in this research is multiple regression analysis, with a total of 99 respondents. The research results showed that the implementation of the Village Information System in Pegajahan District, Serdang Bedagai Regency went very well because it was in a very positive area based on score interpretation. The Human Resources variable (X1) has an average total value of 3.94. The infrastructure variable (X2) has an average total value of 4.00. The institutional and budget variables (X3) have an average total value of 4.00. The IT service variable (X4) has an average total value of 4.06. The influence of the Village Information System which includes the variables Human Resources (X1), facilities/infrastructure (X2), institutions and budget (X3), and IT services (X4) has a positive and significant influence on the acceleration of village development in Pegajahan District, Serdang Bedagai Regency.